Legal Protection for Creditors Regarding Collateral Used by Debtors for Online Gambling Activities in Indonesia - Tri Reni Novita; Tri Putra Rahmad Ramadani (Advances In Social Humanities Research, 2026)
The rapid development of information technology has transformed various economic activities, including the emergence of internet-based gambling practices known as online gambling. This phenomenon has generated significant legal and economic consequences, particularly in creditor-debtor relationships. Debtors involved in online gambling often misuse credit facilities, experience financial instability, and ultimately fail to fulfill their repayment obligations. In several cases, debtors have transferred, encumbered, or misused collateral assets to obtain additional funds for gambling activities. Such circumstances pose substantial risks to creditors and challenge the effectiveness of security law as a legal protection mechanism. This study aims to analyze the legal protection provided by Indonesian security law for creditors regarding collateral assets connected to debtors engaged in online gambling activities. The research employs a normative legal method using statutory, conceptual, and comparative approaches. The primary legal materials include the Indonesian Civil Code, Law Number 42 of 1999 concerning Fiduciary Security, Law Number 4 of 1996 concerning Mortgage Rights, and regulations related to the eradication of online gambling. The findings indicate that Indonesian security law provides strong protection through preferential rights, collateral registration systems, and collateral enforcement mechanisms. Nevertheless, the growth of digital financial transactions and online gambling platforms creates new challenges in monitoring debtor behavior and safeguarding collateral assets. Therefore, strengthening supervisory mechanisms, improving debtor risk assessment systems, and enhancing cooperation between financial institutions and law enforcement agencies are essential to ensure legal certainty and effective creditor protection in the digital era.